2009
DOI: 10.4049/jimmunol.0902550
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Interaction of Human IgG Subtype Immune Complexes with Cells Expressing R and H Allelic Forms of a Low-Affinity Fcγ Receptor CD32A

Abstract: CD32A, the major phagocytic FcγR in humans, exhibits a polymorphism in the ligand binding domain. Individuals homozygous for the R allelic form of CD32A (CD32AR allele) are more susceptible to bacterial infections and autoimmune diseases as compared with H allelic CD32A (CD32AH) homozygous and CD32AR/H heterozygous individuals. To understand the mechanisms behind this differential susceptibility, we have investigated the dynamics of the interaction of these allelic forms of CD32A when they are simultaneously e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 50 publications
(53 reference statements)
3
45
0
Order By: Relevance
“…It seems like the R/R131 allele increases the susceptibility to both bacterial infections and autoimmune diseases, whereas the H/H131 allele does not. The heterozygote R/H131 is phenotypically similar to H/H131 [29]. The R/R131 genotype binds CRP with high affinity, IgG with low affinity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems like the R/R131 allele increases the susceptibility to both bacterial infections and autoimmune diseases, whereas the H/H131 allele does not. The heterozygote R/H131 is phenotypically similar to H/H131 [29]. The R/R131 genotype binds CRP with high affinity, IgG with low affinity.…”
Section: Discussionmentioning
confidence: 99%
“…R/R131 homozygotes bind CRP with high affinity, H/H131 homozygotes with low affinity, and H/R131 heterozygotes with intermediate affinity [13]. Recently, it was shown that the H-allele outcompeted the R-allele when their protein products simultaneously competed for IgG as a ligand [29]. In contrast to CRP, IgG2-binding to FccRIIa is lower in the R131 than in the H131 allotype [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phagocytes can express Fc␥R3a but typically do so at lower levels, relying primarily on Fc␥R2a, which may also bind to a broader array of subclasses, but is insensitive to Fc domain fucosylation, for activity (18,53). Thus, differences in IgG subclass distribution and glycosylation among or even within subclasses (particularly IgG1 and IgG3) within the broader pool of HIV-specific antibodies present in each patient population may lead to altered recruitment of innate immune cell subsets expressing different Fc␥Rs, resulting in the differential antiviral clearance observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether this action plays a role in the generation of secondary Ab responses, we blocked ICs from binding to FcgRs by using CD32-Ig, a recombinant soluble FcgR dimer that binds the Fc regions of ICs with higher avidity than do cell-surface FcgRs (21,22). We immunized cohorts of B6 mice i.p.…”
Section: Ics Stimulate Secondary Responses Through Fcgr Binding Not mentioning
confidence: 99%